The study of difference in alpha and theta band in divergent and convergent thinking in the posterior of the right hemisphere - Sepideh Shahmoradi; Mohammad Reza Zoghi Paydar; Mehran Farhadi; Shahryar Yar Mohammadivasel (مجله علوم روانشناختی)
Background: One of the most influential factors in creativity is brain waves. Among brain waves, alpha and theta waves are considered the most effective in fostering creativity in individuals. Alpha wave activity represents the dominant oscillatory activity of the human brain and is associated with fundamental and complex cognitive functions such as divergent thinking. Previous research has often conceptualized creativity as a cohesive concept that can be assessed using questionnaires, which may not seem sufficient for the underlying mechanism. Aims: The aim of the present study was to investigate the differences in the patterns of alpha and theta brain waves in the posterior regions of the right hemisphere during divergent and convergent thinking. Methods: The current study employed a semi-experimental pre-test-post-test design with a two-month follow-up period. The research population consisted of all graduate students aged 20 to 46 years in psychology and cognitive sciences at Payam Noor University and the Cognitive Sciences Research Institute in 2023. The sample included 32 participants (16 men and 16 women) selected using purposive sampling and randomly assigned to experimental conditions (divergent and convergent). The research instruments included the Chapman Superiority Scale (Chapman, 1987), a 64-channel Ant EEG system, tasks for divergent thinking (snake counting, alternate uses), and tasks for convergent thinking (number counting, Tower of London). Results: The repeated measures analysis of variance showed significant differences between the two study conditions (divergent and convergent) in the posterior region. The difference between divergent and convergent conditions was statistically significant in favor of divergent thinking for both alpha (P< 0.05) and theta (P< 0.01) bands. Conclusion: The findings of the present study can provide a basis for further investigations into brainwave neurofeedback and other quantitative electroencephalogram (QEEG) components, such as absolute power, coherence in other frequency bands, in relation to divergent and convergent thinking differences.